Altered resting-state functional connectivity of raphe nucleus is associated with tremor in Parkinson’s disease - Zheng, Qianyi; Zhang, Dongling; Sun, Junyan; Wang, Junling; Chen, Lili; Wang, Xuemei; Wu, Tao (Frontiers in Aging Neuroscience, 2025)
IntroductionTremor is a prevalent and disabling motor symptom in Parkinson’s disease (PD). The role of the serotonergic system in Parkinsonian tremor remains unclear. We aimed to investigate whether functional connectivity (FC) of the dorsal (DRN) and median (MRN) raphe nuclei is associated with tremor in PD.MethodsForty PD patients with tremor dominant (TD-PD), 42 PD patients with postural instability and gait disturbance dominant (PIGD-PD), and 40 healthy controls (HCs) were enrolled. Resting-state functional MRI was used to investigate altered FC of the DRN and MRN in TD-PD patients compared to HCs and PIGD-PD patients. Subsequently, correlations between FC of the raphe nuclei and motor-related clinical variables were analyzed.ResultsBoth TD-PD and PIGD-PD patients showed reduced FC of the raphe nuclei compared to HCs. TD-PD patients demonstrated a more pronounced reduction in FC for both DRN and MRN across extensive brain regions, such as the sensorimotor cortex, temporal cortex, occipital cortex, and cerebellum, relative to PIGD-PD patients. Correlation analysis revealed that FC of both DRN and MRN was negatively correlated with tremor severity, including the total tremor score, rest tremor scores (amplitude, constancy, and index of severity), and postural tremor score. Our findings indicate significant hypoconnectivity of both DRN and MRN in TD-PD patients. Moreover, both DRN and MRN related functional networks exhibited correlations with tremor severity.DiscussionThese results support the association between serotonergic dysfunction and Parkinsonian tremor, suggesting that both DRN and MRN may play critical roles in the pathogenesis of tremor in PD.